Nanomotors Sense Local Physicochemical Heterogeneities in Tumor Microenvironments. (23rd October 2020) - Dasgupta, Debayan; Pally, Dharma; Saini, Deepak K.; Bhat, Ramray; Ghosh, Ambarish
Abstract: The invasion of cancer is brought about by continuous interaction of malignant cells with their surrounding tissue microenvironment. Investigating the remodeling of local extracellular matrix (ECM) by invading cells can thus provide fundamental insights into the dynamics of cancer progression. In this paper, we use an active untethered nanomechanical tool, realized as magnetically driven nanomotors, to locally probe a 3D tissue culture environment. We observed that nanomotors preferentially adhere to the cancer‐proximal ECM and magnitude of the adhesive force increased with cell lines of higher metastatic ability. We experimentally confirmed that sialic acid linkage specific to cancer‐secreted ECM makes it differently charged, which causes this adhesion. In an assay consisting of both cancerous and non‐cancerous epithelia, that mimics the in vivo histopathological milieu of a malignant breast tumor, we find that nanomotors preferentially decorate the region around the cancer cells. Abstract : Within a reconstructed tumor‐like 3D microenvironment, magnetically driven swarms of nanomotors selectively adhere to the extracellular matrix (ECM) surrounding breast cancer cells in a charge‐dependent manner. The ECM proximal to untransformed breast epithelia does not show adhesion. This principle is relevant for theranostic modalities seeking to localize and target cancer micro‐niches surrounded by healthy tissue.